The mast cell exosome-fibroblast connection: A novel pro-fibrotic pathway - Savage, Alexandria; Risquez, Cristobal; Gomi, Kazunori; Schreiner, Ryan; Borczuk, Alain C.; Worgall, Stefan; Silver, Randi B. (Frontiers in Medicine, 2023)
Introduction In addition to the traditional activation of resident receptors by release of local mediators, new evidence favors the existence of exosomes in cell-to-cell communication that mediates delivery of specific cargo to modulate recipient cell function. We report that mast cell exosomes are an additional source of pro-fibrotic substances and constitute a unique pathway for the generation of excess collagen. Methods We use primary human lung fibroblasts (HLFs) to demonstrate the uptake of labeled exosomes isolated from the human mast cell line HMC-1 (MC-EXOs), previously shown to contain protein cargo in common with human mast cell exosomes. Results The MC-EXO uptake by HLF is to the cytosol and increases both proline hydroxylation in HLF lysate and secreted collagen, within 24 h, which is sustained over 72 h, the same time required for transforming growth factor-β (TGF-β) to activate collagen synthesis in the HLFs. Unlike TGF-β, MC-EXO uptake does not induce fibrillar gene activation or invoke the Smad-nuclear transcription pathway. We show that MC-EXO uptake and TGF-β have an additive effect on collagen synthesis in HLF and postulate that MC-EXO uptake by HLFs is a contributing factor to excess collagen synthesis and represents a unique paradigm for understanding fibrosis. Discussion It is known that, in the lungs, mast cells are more activated and increase in number with inflammation, injury and viral infection associated with fibrosis. With the reported increased incidence of post-COVID-pulmonary fibrosis (PCPF), data from patients with severe COVID-19 are presented that show an increase in the mast cell number in lung parenchyma, the site of PCPF. Our findings provide a rationale for targeting multiple fibrogenic pathways in the management of lung fibrosis and the use of mast cell exosomes as a biomarker for the prognostic and diagnostic management of evolving fibrotic lung disease.